The provision of public planning information and services on the Internet by Irish Local Authorities : a user centric perspective - De Róiste, Mairéad (Trinity College (Dublin, Ireland). Department of Geography, 2007)
The Internet is increasingly used to disseminate local government information and to provide public services. Although this is still a developing area of research, the needs of users of local government information are often overlooked in the research and the benefit of online provision is seldom rigorously tested. This study evaluated the current provision of planning information on the Internet in Irish local authorities from the users' perspective. The provision was evaluated using methods that acknowledge the user's importance in determining the suitability of online information. In this research, the users of the planning information were identified and their characteristics and needs were assessed via an online questionnaire. Finally, local authorities were selected based on the evaluation of the local authority online provision and interviews w ere conducted regarding their views of users and their provision. The provision of online inform ation varies drastically across the different local authorities.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin